2017
DOI: 10.1002/lary.26824
|View full text |Cite
|
Sign up to set email alerts
|

Consulting Dr. Google: Quality of Online Resources About Tympanostomy Tube Placement

Abstract: NA. Laryngoscope, 128:496-501, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
0
37
0
3
Order By: Relevance
“…Prior studies across multiple specialties have evaluated both POEMs and A/V education materials and have found that patient education materials online are often incorrect and/or incomprehensible . The PEMAT specifically has been used most frequently to evaluate and study educational materials in internal medicine literature.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies across multiple specialties have evaluated both POEMs and A/V education materials and have found that patient education materials online are often incorrect and/or incomprehensible . The PEMAT specifically has been used most frequently to evaluate and study educational materials in internal medicine literature.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of studies examining the quality of online otolaryngology content for patients, which is surprising given the number of individuals who are likely to access it. A number of studies have assessed the quality of online medical information, but only a small number have focused on otolaryngological conditions 9 14 …”
Section: Discussionmentioning
confidence: 99%
“…The use of online internet information may prove helpful for the parent’s decision making and understanding their children problems. 23 …”
Section: Discussionmentioning
confidence: 99%